Formulating the alternate archives of produced locality - Karmakar, Goutam (ELOPE (Ljubljana), 2020)
The present paper aims to outline the diasporic consciousness in two Indian diasporic women poets namely, Sujata Bhatt and Debjani Chatterjee. The poets' diasporic consciousness is strewn with the nostalgia for lost homes, pangs of homelessness, fractured identity, the disintegrated historiography of displaced individuals, persistent "post-memory" and continuous struggle to assimilate into the environment of "hostland". This assimilation is achieved by transcending the geographical and psychological borders of "homeland" as seen in the selected poems of Bhatt and Chatterjee. The paper also attempts to show how the poets formulate "alternate archives" by delineating their discourses of displacement (Hirsch and Smith 2002) of produced locality.
Keywords: diasporska zavest; domovina; gostiteljsko okolje; identiteta; nostalgija; spomin